2017
DOI: 10.37828/em.2017.14.11
|View full text |Cite
|
Sign up to set email alerts
|

Ostracods in the Plankton of the Sivash Bay (The Sea of Azov) During Its Transformation From Brackish to Hypersaline State

Abstract: Bay Sivash (the Sea of Azov), the largest lagoon in Europe, demonstrates a sharp ecosystem change due to anthropogenic impact. A pronounced salinity increase occurs as a result of the decision to stop supplying Dnieper water into the North-Crimean Canal. Salinity has increased from 20–22 g/L to 55–75 g/L in the lagoon. This led to the changes of biotic composition. The authors used data on ostracod species composition and abundance in samples of 2014–2016 samples with comparison with data from samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…in some samples (Drapun et al, 2017). Similar trends in the changes of the bottom meiobenthos were observed in the Aral Sea during a long-term salinity increase from brackish water up to 88-109 g l À1 (Mokievsky, 2009).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…in some samples (Drapun et al, 2017). Similar trends in the changes of the bottom meiobenthos were observed in the Aral Sea during a long-term salinity increase from brackish water up to 88-109 g l À1 (Mokievsky, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…In 2015, the average contribution of Ostracoda to the total abundance of the bottom meiobenthos was 17% varying from <1 to 56% in the samples . In 2015, ostracods were also abundant in plankton, dominating FO À frequency of occurrence; D À species was dominant; SD À species was subdominant; 1data from Kolesnikova et al, 2017 andDrapun et al, 2017;2 -data for 2004; ** À found only in the plankton samples at salinity of 30 g l À1 ; * À found only in the plankton samples at salinity of 52 g l À1 ; *** À found only at salinity of 30 g l À1 ; **** À without species found only at salinity 30 g l À1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Какая часть этой первичной продукции потребляется в озере гетеротрофами, а какая захоранивается в донных отложениях? В крымских гиперсоленых водоемах, включая озеро Херсонесское, в матах нитчатых зеленых водорослей наблюдали очень высокие численности животных и инфузорий, намного превышающие таковые в планктоне (Ivanova et al, 1994;Kolesnikova et al, 2008;Павловская и др., 2009;Шадрин и др., 2016;Drapun et al, 2017;Kolesnikova et al, 2017;Shadrin et al, 2017). Зная средние размеры животных и хорошо известные зависимости массы тела от его длины, интенсивности метаболизма и скорости роста от массы тела в различных группах беспозвоночных животных (Винберг, 1979;Ivanova et al, 1994;Балушкина и др., 2009), можно рассчитать примерный суммарный рацион, животных, обитающих в матах.…”
unclassified